COMPARISON OF APICAL LEAKAGE VALUE BETWEEN EUCALYPTOL AND ORANGE OIL AS GUTTA PERCA SOLVENT - Sherli Diana; Rizki Sri Yuliati; Bayu Indra Sukmana (FKG Unlam, 2021)
Background: The success or failure of root canal treatment is influenced by anatomical factors of the root canal, bacterial infection that causes inadequate hygiene, formation and filling of root canals, iatrogenic factors and several other factors. The average success of root canal treatment is 86-95%, while the failure of canal treatment ranges from 5-14%. Root canal re-treatment can be performed in the event of failure of root canal treatment. The method that can be used is gutta percha solvent. The gutta percha solvents used were Chloroform, Eucalyptol, Orange Oil, and Xylene, but chloroform has been categorized as a carcinogenic substance. Guta percha solvent can cause the intercrystalline distance to be larger, so that it can damage the apical density at obturation. This can create a gap between the gutta percha and the sealer which can cause apical leakage. Objective: To compare the value of apical leakage after root canal re-treatment between gutta percha solvent eucalyptol and orange oil. Method: The research method used is True Experimental with post-test only with control group design. A minimum sample of 8 teeth in a group. Total samples from all groups were 24 teeth. The teeth were stained using methylene blue and measured using stereomycroscopes. Results: the highest mean apical leakage was eucalyptol (4.55±2.59), xylene (2.77±1.94), and the lowest was citrus oil (2.20 ±1.06). The results of One-Way ANOVA test showed that there were no significant differences between orange oil, eucalyptol, and xylene (positive control). Conclusion: Eucalyptol has a higher average apical leakage value compared to orange oil and Xylene after root canal re-treatment as a gutta percha solvent. There was no significant difference between orange oil, Eucalyptol, and Xylene.Keywords: Apical leakage, eucalyptol, orange oil